Kajian Hadis Missoginis tentang Iddah - Imam Supriyadi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
Recent studies on women have begun to poke around the "classical women's interpretation" from the understanding of previous scholars. Concretely, studies on women today often produce misogenic conclusions, in the form of placing women in a low position and full of responsibility. One of them is related to the "provision of iddah period for women", especially for women whose husbands died while pregnant. The first conclusion of this paper is that there is a "provision of 'iddah" as a waiting period which is only mandatory for women because' iddah functions to wait for certainty about the cleanliness of a woman's womb from her fetus, which of course will make it clear that children born in her iddah period have no relationship nasab with the next husband. Thus, the application of the provisions of 'iddah and ih}da>d for these women is far from the missogynist which is often propagated by the feminimism movement. The second conclusion is that a pregnant woman whose husband died is until the delivery is complete, because the hadith narrated by al-Tirmidhy number 1193 eliminates the confusion of friends who are in dispute about this as in the history of hadith number 1194.